Энергосбережение как основной фактор охраны окружающей среды - Кузин, А. К. (НТУ "ХПИ", 2004)
Energy-saving is considered as the way to reduce negative impact of power-engineering on environment. Tendencies of changes of main parameters of energy-saving (changes in gross domestic product, final energy consumption and energy intensity dynamics) in NIS, countries of Central and Eastern Europe and EU are considered. By the examples of EU and Russia, performance of policy on energy-saving increase on national level is shown
Keywords: энергетика; энергия; энергоэффективность; энергоемкость; Орхусская конференция